The Effect of Integrating the Claim–Evidence–Reasoning Framework into the Argument-Driven Inquiry Model on Students’ Scientific Argumentation Skills and Green Chemistry Learning Outcomes - Risna Amalia; Ramlahwati Ramlahwati; Halimah Husain (Journal La Edusci, 2026)
This study aimed to describe the level and improvement of students’ scientific argumentation skills and learning outcomes and to examine the effect of integrating the Claim–Evidence–Reasoning (CER) framework into the Argument-Driven Inquiry (ADI) learning model in green chemistry. A quasi-experimental method with a nonequivalent pretest–posttest control group design was employed. The participants were 60 Grade X students at SMAN 13 Makassar, comprising 30 students in the experimental class taught using CER-integrated ADI and 30 students in the control class taught using ADI without explicit CER integration. Data were collected through a scientific argumentation essay test and a multiple-choice learning-outcome test. The data were analyzed using descriptive statistics, N-Gain, an independent-samples t-test, and the Mann–Whitney U test. The experimental class obtained a higher scientific argumentation posttest mean than the control class (51.10 vs. 48.07), with N-Gain scores of 0.70 and 0.64, respectively, both categorized as moderate. The experimental class also achieved higher percentages in claim, evidence, and reasoning. For learning outcomes, the experimental class obtained a higher posttest mean (12.40 vs. 11.63), although the N-Gain scores were similar and categorized as moderate (0.55 vs. 0.56). Significant differences were found in scientific argumentation skills (t = −3.410, p = 0.001) and learning outcomes (U = 310.500, p = 0.035). Therefore, CER-integrated ADI significantly supported students’ scientific argumentation skills and learning outcomes in green chemistry.